Postcolonial Qur'anic Studies: Reconstructing Contextual Tafsir as a Decolonial Framework for Resisting the Colonial Legacy - Achmad Napis Qurtubi; Khazri Osman; Youcha Alassane Touré (Tribakti: Jurnal Pemikiran Keislaman, 2026)
The legacy of colonialism has shaped Qur'anic studies through the dominance of Orientalist and Eurocentric methodologies that have marginalized the epistemic authority of the Islamic exegetical tradition. Although postcolonial Qur'anic studies have developed considerably, existing scholarship has largely focused on critiquing Orientalism without formulating contextual tafsir as a postcolonial epistemological framework integrated with maqāṣid al-sharīʿah. This study aims to examine how contextual tafsir can function as a methodology for decolonizing Qur'anic studies while reconstructing the epistemic authority of Islamic interpretation. Employing a library-based research design with an interpretive approach, the study applies thematic analysis of Qur'anic verses, examines their asbāb al-nuzūl (occasions of revelation), and critically engages with the literature on contextual tafsir, postcolonial theory, and maqāṣid al-sharīʿah. The findings demonstrate that the decolonization of Qur'anic studies requires the integration of three interrelated components: postcolonial critique as an analytical instrument for exposing epistemic domination, contextual tafsir as an interpretive methodology that connects the Qur'anic text with contemporary social realities, and maqāṣid al-sharīʿah as a normative framework that directs interpretation toward justice, public welfare, the protection of human dignity, and the common good. The integration of these three components produces an epistemological framework that shifts Qur'anic studies beyond reductionist historical-philological approaches toward a contextual, normative, and transformative paradigm of interpretation. This study proposes an integrative model of postcolonial contextual tafsir as a theoretical contribution to the decolonization of Qur'anic studies and to strengthening the epistemic sovereignty of the Islamic exegetical tradition in addressing contemporary challenges.